Embedded accelerators - Thambipillai Srikanthan. (2009)
The main objective of this project was to develop techniques for accerlaration of algorithms for embedded systems. To achieve this objective, methodologies were developed to perform architecture centric algorithm development. In addition techniques were developed to exploit VLSI arrays for embedded acceleration. In the developed methodologies, algorithms were developed from the perspective of embedded architectures. Developed techniques were applied to algorithms for image processing. Major improvements were observed in the performance of these algorithms in embedded systems environment.